Café Therapy: Integrating Mental Health Care with Organizational Resilience - Maspul, Kurniawan Arif (Fakultas Ekonomi dan Bisnis, 2024)
Café Therapy is a novel technique that blends the convenience of coffee shop settings with counseling and therapy services, with the goal of making mental health care more accessible and stigma-free. Café Therapy not only creates additional money but also lowers barriers to getting treatment and builds social resilience through community ties by integrating mental health services into a popular and friendly coffee shop setting. This novel idea is consistent with community psychology ideas, emphasizing the need of addressing social concerns and developing support networks. Café Therapy intends to improve its effectiveness and scalability through in-depth interviews, observations, and literature research, ultimately enhancing mental health outcomes and community resilience. Café Therapy creates a holistic and supportive environment that benefits individuals and the community as a whole by providing a safe space for therapy sessions, offering group programs and workshops, promoting nutritious food and relaxation, and collaborating with local mental health organizations.